Bibliometric Study On The Use Of Information And Communication Technologies In Water Resources Management - Pinheiro, Marcus Vinícius Chiulle; Georges, Marcos Ricardo Rosa; Falsarella, Orandi Mina (ANAP Brazil, 2021)
ABSTRACT Sustainability is a topic that has great relevance and is based on three main dimensions: social, environmental, and economic. It is known that one of the most important and finite elements on the planet is water. In the context of sustainability, water is a resource responsible for sustaining people who survive from primary, secondary, and tertiary activities, such as agriculture, livestock, and basic human needs. It is also noticed the existence of a lot of data and information related to water, such as retention, storage, collection, treatment, distribution, consumption, and return. After addressing the importance of this element or after exemplifying the importance of this element, a discussion is generated on the sustainable management of water resources in river basins and the help that Information and Communication Technologies (ICT) can contribute to the decision-making process of water resources management. Thus, in view of the actors (people who survive from primary, secondary, and tertiary activities) and data being produced from different sources and of high complexity involved, it is interesting a study based on understanding how modern ICT are helping the process of decision-making in the management of water resources in the public sphere, especially in relation to the management of river basins. Therefore, the objective of this work is to research how the application of ICT has been used in the management of water resources. To achieve this goal, this work will carry out a bibliometric study. This bibliometric study will be done using the following key words combined with each other: Water Resources Management, Decision Support System, Information and Communication Technologies, Big Data. In view of this, the database chosen for the research is Scielo. The initial results obtained will be filtered to exclude non-pertinent works and repeated results. After evaluating the relevance of the initial results, the selected articles will be studied and classified according to several criteria, such as: which technology is mentioned, which aspect of water management was used, in which watershed was applied, in addition to year of publication, journal, authors, institution, research methods used and area of ​​study. Through the aid of an electronic spreadsheet, the data will be tabulated, graphs and descriptive statistics will be generated. From these results, analyzes will be made of how the scientific production in relation to the use of ICT in the management of water resources in the hydrographic basins that have been used. KEY WORDS: Sustainability. Management of water resources. Decision support system. Technologies of information and communication. Big data.